Tinjauan Yuridis Tentang Penerbangan Balon Udara Sebagai Tradisi Budaya Masyarakat di Kabupaten Ponorogo - Khoirul Bariyah; Helmy Boemiya (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The country of Indonesia has a lot of cultural diversity, both language, social, ethnicity, race, religion in each of its regions. One of them is related to the culture that exists in Indonesia, namely the tradition of flying hot air balloons. In some areas in Indonesia this is made as an annual community tradition, for example in Ponorogo Regency. This community raises problems such as the emergence of cases that harm the community, giving rise two problem formulations how to regulate positive law on hot air balloon flights in Indonesia, and how the Ponorogo Regency’s regional policy relates to the use of hot air balloons as a cultural tradition of the community. The type of research used is normative or doctrinal legal research, using a statutory approach. The results of the study indicate that regulations related to hot air balloon flights in Indonesia can be proven through regulations that have been established based on the hierarchy of formation. These are ordered from the highest to the lowest regulations, namely Law Number 1 or 2009 concerning Aviation, Minister of Transportation Regulation Number 40 of 2018 concerning the Use of Hot Air Balloons in Community Cultural Activities, and regional regulations at the provincial or district/city level in Indonesia. There is no policy in the form of a regional regulation related to hot air balloon flights in Ponorogo Regency, until now the policy is in the form a Regent’s Circular.